Mixed Epithelial and Stromal Tumor Family of Kidney (Adult Cystic Nephroma, Mixed Epithelial and Stromal Tumor): Retrospective Clinicopathological Evaluation - Hale DEMIR; Zehra SAHIN; Oktay OZMAN; Muhammed DEMIRBILEK; Sami Berk OZDEN; Iclal GURSES; Haydar DURAK; Nesrin UYGUN; Bulent ONAL (Federation of Turkish Pathology Societies, 2022)
Objective: Tumors belonging to the mixed epithelial stromal tumor family (MESTF) are rare; thus clinicopathological experience about them are limited. Each epithelial and stromal component shows different patterns in these tumors. Material and Method: Clinicopathological features of 11 MESTF cases that were diagnosed between 2000 and 2021 at a single center were evaluated. Results: Ten of the 11 patients were female (F:M = 10:1). The mean age of the females was 47 (31-63) years; the male patient was 45 years old. The mean tumor diameter was 6.7 (3.5-19) cm. All tumors had varying proportions of cystic and solid components. Eight cases were well circumscribed, and the others had distinct but irregular borders. Two of the tumors with irregular borders were bulging into the renal sinus. The epithelial component was dominant in most cases. In the epithelial component, macrocyst, microcyst, and tubules were the most common patterns and the most common types of lining epithelium were flat, cuboidal and hobnail. The stromal component was variable in most cases and included hypocellular (mostly collagenous) and cellular areas. In most cases, the cellular stroma had an ovarian-like appearance. Among the other features observed, hyalinization and dystrophic calcification were common. The positivity for estrogen and progesterone receptor in the stromal component was observed in almost all female cases. Conclusion: MESTF, which has distinctive features, should be considered in the differential diagnosis of cystic kidney tumors.